2017 IEEE World Haptics Conference (WHC) 2017
DOI: 10.1109/whc.2017.7989889
|View full text |Cite
|
Sign up to set email alerts
|

Optimal skin impedance promotes perception of ultrasonic switches

Abstract: International audienceUltrasonic friction reduction is one potential technology for bringing tangibility to flat touchscreens. We previously established that this approach can be used to create an artificial sensation of pressing a mechanical switch by varying the coefficient of friction, which depends on the force applied by the user. This sensation proves effective majority of, but a non-negligible fraction reported feeling only weak sensations or none at all. In the present study, we examined the factors po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 17 publications
2
12
0
Order By: Relevance
“…Although, the earlier studies have investigated the contact mechanics of friction [5], [10]- [17] and our perceptual ability to discriminate two different surfaces based on friction [18]- [20], the number of studies investigating the intermittent contact mechanics during a change in friction on a touch surface is very limited [21]- [24]. Furthermore, the factors affecting our tactile perception of this change have not been investigated in depth yet [22]- [26].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although, the earlier studies have investigated the contact mechanics of friction [5], [10]- [17] and our perceptual ability to discriminate two different surfaces based on friction [18]- [20], the number of studies investigating the intermittent contact mechanics during a change in friction on a touch surface is very limited [21]- [24]. Furthermore, the factors affecting our tactile perception of this change have not been investigated in depth yet [22]- [26].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the studies on sliding-finger, it has been shown that a click effect, as in key press, can be created by reducing the friction as the user presses on an ultrasonically actuated touch surface [23], [26], [30], [31]. Tashiro et al [30] have rendered the feeling of buckling and restitution of mechanical buttons using Langevin-type ultrasonic transducer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10.b) when compared to the vibratory transfer function V . The variability between plate vibration and friction reduction efficiency reflects differences in the bio-mechanical properties of the finger skin, which were also observed in [45] and have been shown to significantly affect subjects' perception [46]. Therefore, stimuli generation on surface haptics should focus on controlling the frictional force and friction coefficient rather than the ultrasonic amplitudes, as proposed in [47], [48].…”
Section: Discussionmentioning
confidence: 99%
“…Users detected more easily the falling friction than the rising friction and reported to feel it as a convincing keyclick sensation. The proposed method relies on sudden changes in the impedance of the finger [13], which are provoked by the influence of the ultrasonic lubrication [19,16] on the compression of the fingerpad. Lateral motion of the finger is generally necessary to the occurrence of friction modulation by ultrasonic lubrication.…”
Section: Earlier Workmentioning
confidence: 99%